Outliers and influence points in German business cycles - Manuela Zucknick; Claus Weihs; Ursula Garczarek (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
In this paper, we examine the German business cycle (from 1955 to 1994) in order to identify univariate and multivariate outliers as well as influence points corresponding to Linear Discriminant Analysis. The locations of the corresponding observations are compared and economically interpreted.
Keywords: 519; outliers; influence points; linear discriminant analysis; business cycles; Konjunktur; Zeitreihenanalyse; Deutschland; Diskriminanzanalyse